Nanoindentation characterization of nano-twinned grains in an austenitic stainless steel. (February 2016) - Yan, F.K.; Zhang, B.B.; Wang, H.T.; Tao, N.R.; Lu, K.
Abstract: Nano-twinned austenite grains were characterized in an austenitic stainless steel by using nanoindentation. The nano-twinned austenite grains exhibit identical elastic modulus with the micro-sized recrystallized austenitic grains. Nanoindentation hardness of the nano-twinned grains is about 4.5 GPa, ∼1.0 GPa higher than that of the recrystallized grains, but lower than that of the nano-sized grains with the comparable size owing to the presence of twinning partial dislocations.